Composite film, packaging material containing composite film, packaging mode and application of packaging material
By designing a heat-sealed anti-adhesive layer containing anti-adhesive materials, inorganic filler A and ultra-high molecular weight polyethylene in the food packaging composite film, the problems of insufficient anti-adhesive performance and food safety risks in the prior art are solved, and better anti-adhesive performance and food preservation effects are achieved.
Patent Information
- Application Number
- CN202510130994.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2045-02-06
AI Technical Summary
The existing food packaging composite films have insufficient anti-adhesion performance when packaging candies, problems with peeling strength and oil resistance of adhesive and heat sealing layers in oily candy packaging, and pre-coated glue may migrate to food, which poses food safety risks.
A heat sealed anti-adhesive layer is designed, containing anti-adhesive materials (such as organic silicon compounds), inorganic filler A and ultra-high molecular weight polyethylene. Through the combination of these materials, a micro-nano-sized film concave and convex surface is formed to reduce surface tension and improve anti-adhesive performance.
It effectively improves the anti-stick performance of the inner layer of the composite membrane to candy, maintains the integrity of candy or other foods, extends the shelf life, and avoids the food safety risks of glue migration.
Smart Images

Figure CN119567687A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of food science and technology, and specifically relates to a composite film and a packaging material, a packaging method and an application thereof comprising the composite film. Background Art
[0002] Food packaging composite film refers to a film made of two or more different material layers through a certain process method. It is used to package food and plays a role in protecting, preserving and extending the shelf life of food.
[0003] At present, there are several methods to study the material structure of commonly used food packaging composite films: 1. Single-layer structure: a packaging film composed of one material, such as polyethylene (PE), polypropylene (PP), polyester (PET), etc. The single-layer structure is simple and easy to prepare, but the oxygen permeability and moisture permeability are poor, and it is not suitable for long-term storage and food with high preservation requirements. 2. Double-layer structure: a packaging film composed of two different material layers, one of which has certain oxygen permeability and moisture permeability, which can be used to increase the preservation performance of the packaging film. Common double-layer structures include polyethylene / polyester (PE / PET), polyethylene / polypropylene (PE / PP), etc. 3. Three-layer structure: a packaging film composed of three different materials, one of which has good oxygen permeability and moisture permeability, which is used to increase the preservation performance of the packaging film, and there is also a barrier layer to block the penetration of moisture, oxygen and other harmful substances. Common three-layer structures include polyethylene / nylon / polyester (PE / NV / PET), polyethylene / polyvinyl alcohol / polyethylene (PE / EVOH / PE), etc.
[0004] For candy packaging, most of them are currently packaged in composite films similar to other foods. However, first, candy has great stickiness, especially water-in-oil gel candy, which will have serious stickiness with the inner layer of the composite film. Currently, the main products on the market are to apply some edible oils on the composite film in advance to prevent the candy from sticking. This method will increase the greasy feeling of the product, leaving a negative impression on the consumer, thereby reducing the initiative to consume. In addition, the coated oil is easy to contaminate the heat-sealing area of the composite film during the packaging process, causing the package to leak, which will cause the candy to deteriorate during the shelf life. Second, during the long-term storage of aluminum foil pre-coated with glue and acidic food, the glue will gradually migrate into the food. The total migration amount of the acidic food simulation liquid of the aluminum foil is much greater than the national standard limit, which poses a food safety risk. Third, due to the packaging of oily candies, the peel strength and oil resistance of the adhesive and heat-sealing layer also need to be solved. Summary of the invention
[0005] In order to solve the problems and shortcomings in the prior art, the present invention provides a composite film and a packaging material and packaging method comprising the composite film, and its application in packaging. The composite film is designed with a heat-sealed anti-sticking layer, which effectively improves the anti-sticking performance of the inner layer of the composite film to candies or other foods. And the composite film has good tearing performance when used to package candies or other foods. After tearing, the candies or other foods remain intact without obvious damage.
[0006] According to a first aspect of the present invention, a composite film is provided, comprising a heat-sealable anti-sticking layer; the heat-sealable anti-sticking layer comprises an anti-sticking material, an inorganic filler A, a polyolefin A, and an ultra-high molecular weight polyethylene; and the anti-sticking material comprises an organic silicon compound.
[0007] In the composite film provided by the present invention, the heat-sealing anti-adhesive layer contains anti-adhesive materials such as silicone compounds such as siloxane polymers or siloxanes, and also contains micron-level inorganic fillers A. First, the inorganic fillers provide micron-sized concave-convex points, and the organic siloxane polymer materials are incompatible with polyolefins such as PE, forming nano-sized concave-convex points on the surface, thereby forming a micro-nano-sized film concave-convex surface; second, at the same time, there are siloxane organic substances in the organic material, which can greatly reduce the surface tension of the material, thereby playing an anti-adhesive role. In addition, micron-level ultra-high molecular weight polyethylene is also introduced into the heat-sealing anti-adhesive layer. The ultra-high molecular weight polyethylene will not be melted during the melting process of the film layer preparation, and the thermal stability is also high. Therefore, the ultra-high molecular weight polyethylene particles can supplement the depressions of the micron material in the blown film (the ultra-high molecular weight polyethylene particles will float on the surface of the film), further improving the protruding structure on the surface of the film layer, and reducing the surface tension of the film layer.
[0008] The combined effect of the above aspects results in a large number of microscopic protrusions on the surface of the inner layer of the composite layer (heat-sealing anti-sticking layer), which are mainly caused by large particles floating on the surface. This effectively reduces the surface tension of the inner layer of the composite layer (heat-sealing anti-sticking layer), and further effectively reduces the contact angle between the candy or other food and the inner layer of the composite film, making the inner layer of the composite film have better anti-stick properties for candy, especially water-in-oil gel candy, and can effectively maintain the integrity of the candy or other food after opening the package.
[0009] At the same time, the composite film prepared using the above-mentioned heat-sealed anti-sticking layer has suitable tearing properties, that is, it has relatively suitable tearing resistance. It should not be too high or too low. If it is too high, it is not easy to puncture or tear, and if it is too low, it will easily break during the packaging process or other transportation processes, which is not conducive to processing, nor is it conducive to the protection and preservation of candy.
[0010] Preferably, the melting point of the polyolefin A is not less than 105°C; the melting point of the ultra-high molecular weight polyethylene is not less than 130°C, and the melt index is not higher than 0.05. Considering that hot filling is often used when packaging candies or other foods, the above polyolefins and ultra-high molecular weight polyethylene, i.e., heat-resistant polyolefins (due to the high filling temperature of such candies, the heat resistance requirements of polyethylene need to be considered. Taking polyethylene as an example, 105°C is a watershed. Those with a melting point below 105°C are non-heat-resistant types, and usually metallocenes and other substances that reduce the melting point are added. Those above 105°C are heat-resistant types) are selected so that the material will not soften during the filling process, thereby causing the surface energy and surface microscopic failure of the material.
[0011] Preferably, the mass ratio of the anti-adhesive material, the inorganic filler A, the polyolefin A, and the ultra-high molecular weight polyethylene is 2-30:1-10:50-80:1-10. Controlling the mass ratio of various raw materials of the heat-sealing anti-adhesive layer within a certain range is conducive to better synergy between the raw materials, so that the prepared heat-sealing anti-adhesive layer has lower surface tension, higher thermal stability, and the property of maintaining its surface structure unchanged for a longer period of time, thereby optimizing the long-term anti-adhesive performance. At the same time, this is conducive to making the final heat-sealing anti-adhesive layer have more specific and appropriate burst resistance, which is more conducive to the comprehensive performance of the composite film.
[0012] Preferably, the organosilicon compound comprises a siloxane polymer.
[0013] Preferably, in the heat-sealing anti-sticking layer, the anti-sticking material such as silicone polymer has a melting point of 80-150° C. and a density of 0.9-1.1 g / cm³.
[0014] Preferably, in the heat-sealable anti-sticking layer, the D50 of the inorganic filler A is 1-10 μm; the inorganic filler A includes silicon dioxide. The inorganic filler A in the above particle size range can ensure that the surface of the inner layer (heat-sealable anti-sticking layer) of the composite layer has sufficient micro-nano particle protrusions to reduce its surface energy, and improve the anti-sticking performance of the surface of the inner layer (heat-sealable anti-sticking layer) of the composite layer to candies, especially water-in-oil gel candies and other foods. At the same time, such a particle size distribution is conducive to being fully and evenly dispersed in the polymer, and is more conducive to the relevant performance of the inorganic filler A in the film layer.
[0015] Preferably, in the heat-sealable anti-adhesive layer, the D50 of the ultra-high molecular weight polyethylene is 1-40 μm. Similarly, such a particle size range is conducive to ensuring that the surface of the inner layer of the composite layer (heat-sealable anti-adhesive layer) has sufficient micro-nano particle protrusions to reduce its surface energy, and can also play a good matching role with the inorganic filler A, and can further optimize the anti-adhesive performance of the film layer.
[0016] Preferably, the ultra-high molecular weight polyethylene has a melting point of 130-160° C. and a density of 0.93-0.97 g / cm³.
[0017] Preferably, the ultra-high molecular weight polyethylene is spherical or micro-spherical in shape. The ultra-high molecular weight polyethylene can still maintain its original spherical or micro-spherical shape after the film layer is formed, which is more conducive to a good matching effect with the inorganic filler A, and can further optimize the anti-sticking property and other properties of the film layer.
[0018] Preferably, in the heat-seal anti-adhesive layer, the polyolefin A independently includes at least one of polyethylene and polypropylene. Polyethylene and polypropylene, as the main polymer materials of the packaging composite film, have high transparency, good mechanical properties, heat resistance and low temperature resistance, as well as a wide range of application fields and environmental protection, and can meet various different usage requirements.
[0019] Preferably, in the heat-seal anti-sticking layer, when polyolefin A includes polyethylene, polyethylene includes low-density polyethylene and metallocene polyethylene, and the mass ratio of low-density polyethylene and metallocene polyethylene is 20~60:20~60; or, polyethylene includes low-density polyethylene and linear low-density polyethylene A, and the mass ratio of low-density polyethylene and linear low-density polyethylene A is 20~60:20~60; when polyolefin A includes polypropylene, polypropylene includes homopolymer polypropylene, binary material and ternary material, and the mass ratio of homopolymer polypropylene, binary material and ternary material is 10~30:20~30:40~60; binary material includes polyolefin material formed by copolymerization of two monomers; ternary material includes polyolefin material formed by copolymerization of three monomers. Using the above-mentioned polyolefin to prepare the heat-seal anti-sticking layer is conducive to making the heat-seal anti-sticking layer uniform and dense, having good processing performance and mechanical properties, and is conducive to forming a better micro-nano structure on the surface, so that its lower surface energy can be stably maintained for a long time, that is, providing an anti-sticking effect for a long time, and improving its ability to preserve food such as candy.
[0020] Preferably, the ternary material includes block polypropylene and a rubber component.
[0021] Preferably, in the heat-sealing anti-adhesive layer, when the polyolefin A includes polyethylene, the polyethylene includes low-density polyethylene and metallocene polyethylene, the melting point of the low-density polyethylene is 65-125°C, the melt index is 1-20, and the density is 0.91-0.94 g / cm³; the melting point of the metallocene polyethylene is 80-130°C, the melt index is 1-10, and the density is 0.88-0.93 g / cm³; or, the polyethylene includes low-density polyethylene and linear low-density polyethylene A, the melting point of the low-density polyethylene is 65-125°C, the melt index is 1-20, the density is 0.91-0.94 g / cm³, and the linear low-density polyethylene is The melting point of polyethylene A is 80~125℃, the melt index is 1~20, and the density is 0.88~0.93g / cm³; when polyolefin A includes polypropylene, polypropylene includes homopolymer polypropylene, binary material and ternary material; the melting point of homopolymer polypropylene is 150~170℃, the melt index is 1~10, and the density is 0.88~0.92g / cm³; the melting point of binary material is 135~150℃, the melt index is 1~10, and the density is 0.88~0.92g / cm³; the melting point of ternary material is 135~170℃, the melt index is 1~10, and the density is 0.88~0.92g / cm³.
[0022] Preferably, the composite film further comprises an intermediate barrier layer; the intermediate barrier layer comprises an inorganic filler B and a polyolefin B, and the mass ratio of the inorganic filler B to the polyolefin B is 10-80:20-90. The intermediate barrier layer is combined by adding micron inorganic filler B and polyolefin B, and part of it will protrude during the film blowing process, thereby further affecting the apparent effect of the heat-sealing anti-sticking layer, so that the surface of the heat-sealing anti-sticking layer presents a more obviously protruding micro-nano structure. Under the mass ratio of the above-mentioned raw materials, it can be ensured that a certain amount of inorganic particles B protrude so that part of it protrudes during the film blowing process, and at the same time, the relevant properties of the intermediate barrier layer can be taken into account, so that the intermediate barrier layer and the heat-sealing anti-sticking layer can be better combined, and at the same time, the performance of the composite product film in all aspects is effectively guaranteed.
[0023] Preferably, in the intermediate barrier layer, the inorganic filler B includes at least one of calcium carbonate, talc, mica, and silicon dioxide; the particle size of the inorganic filler B is not less than 1250 mesh; and the polyolefin B independently includes at least one of polyethylene and polypropylene. The particle size of the inorganic filler B is within the above range, which can ensure that the protruding structure in the film blowing process has a suitable protrusion, which can effectively enhance the apparent effect of the heat-sealing anti-sticking layer, and prevent these protruding parts from affecting the composite effect of the intermediate barrier layer and the heat-sealing anti-sticking layer. Polyethylene and polypropylene, as the main polymer materials of the packaging composite film, have high transparency, good mechanical properties, heat resistance and low temperature resistance, as well as a wide range of application fields and environmental protection, which can meet various different usage requirements.
[0024] Preferably, the particle size of the inorganic filler B is 2000-10000 mesh.
[0025] Preferably, the intermediate barrier layer also includes a first compatibilizer and a lubricant; the mass ratio of inorganic filler B, polyolefin B, first compatibilizer, and lubricant is 10~80:20~90:1~30:0~5; the first compatibilizer includes at least one of maleic anhydride modified polyolefin and acrylic acid modified polyolefin; the lubricant includes at least one of calcium stearate, magnesium stearate, and polyethylene wax. Adding a certain amount of compatibilizer is conducive to the full and uniform mixing of inorganic fillers and polymer materials, and improving the overall uniformity of the film layer. At the same time, due to the processing characteristics of inorganic fillers, adding a certain amount of lubricant is conducive to the inorganic fillers and polymer materials being more easily processed into a uniform mixed system, so that the obtained film layer has better quality.
[0026] Preferably, in the middle barrier layer, the polyolefin B has a melting point of 80-160° C., a melt index of 1-100, and a density of 0.88-1.0 g / cm³.
[0027] Preferably, in the middle barrier layer, polyolefin B includes low-density polyethylene B-1 and metallocene polyethylene B-1; or, polyolefin B includes low-density polyethylene B-1 and low-density linear polyethylene resin B-1. Preferably, the mass ratio of low-density polyethylene B-1 to metallocene polyethylene B-1 is 20-70:20-70; or the mass ratio of low-density polyethylene B-1 to low-density linear polyethylene resin B-1 is 20-70:20-70.
[0028] Preferably, in the intermediate barrier layer, the first compatibilizer has a melting point of 80-160°C, a melt index of 1-100, and a density of 0.88-1.0 g / cm³. It should be noted that the compatibilizer is also called adhesive polyolefin or cohesive polyolefin.
[0029] Preferably, in maleic anhydride modified polyolefin, the grafting rate of maleic anhydride is 0.1-5%; in acrylic acid modified polyolefin, the grafting rate of acrylic acid is 2-10%. The introduction of maleic anhydride or acrylic acid graft modified polyolefin can improve the adhesion between layers and avoid delamination. The grafting rate determines the adhesion between layers. If it is too low, the adhesion between layers is poor, but if it is too high, it will affect the melting point, mechanical strength and processing performance of the polymer material, affect the interaction force inside the material, and thus reduce the overall performance of the material.
[0030] Preferably, the composite film further comprises a bonding layer, the bonding layer comprises polyolefin C and a second compatibilizer, and the mass ratio of polyolefin C to the second compatibilizer is 10-90:10-90. The bonding layer is used to bond with the aluminum foil through the adhesive, and the second compatibilizer (adhesive polyolefin) in the bonding layer can play a bonding role between the bonding layer and the intermediate barrier layer, thereby preventing delamination problems caused by stretching after heat sealing.
[0031] Preferably, in the bonding layer, the polyolefin C independently includes at least one of polyethylene and polypropylene.
[0032] Preferably, in the bonding layer, the melting point of polyolefin C is 65-125°C, the melt index is 1-40, and the density is 0.88-0.93 g / cm³; the melting point of the adhesive polyethylene is 65-125°C, the melt index is 1-100, and the density is 0.88-1.0 g / cm³.
[0033] Preferably, in the bonding layer, the polyolefin C comprises low-density polyethylene C-1 and low-density linear polyethylene resin C-1. Preferably, the mass ratio of low-density polyethylene C-1 to low-density linear polyethylene resin C-1 is 20-70:20-70.
[0034] By controlling the melting point, melt index and density of the raw materials for preparing each layer of the composite film of the present invention, such as the heat-sealable anti-layer, the intermediate barrier layer and the bonding layer, within a certain numerical range, the composite film finally obtained can take into account multiple properties such as thermal stability, processing performance and tear resistance, so that the composite film has better comprehensive performance. At the same time, when these layers of materials are used in combination of two or three layers, the composite materials can have strong mutual adhesion and good cohesive strength, and will not be easily delaminated during the heat-seal stretching process, which will affect the use of the composite film.
[0035] Preferably, the second compatibilizer includes at least one of maleic anhydride-modified polyolefin and acrylic acid-modified polyolefin.
[0036] Preferably, the second compatibilizer has a melting point of 80-160°C, a melt index of 1-100, and a density of 0.88-1.0 g / cm³. It should be noted that the compatibilizer is also called adhesive polyolefin or cohesive polyolefin.
[0037] Preferably, the thickness of the composite film is 15-100 μm, and the thickness ratio of the bonding layer, the intermediate barrier layer, and the heat-sealing anti-sticking layer is 1-3:1-5:1-3. Ensuring that the thickness of each layer is within the above range, on the one hand, is conducive to the composite film having a certain mechanical strength and density, and effectively preserving candy and other foods; on the other hand, it can also make the prepared composite film have good tearing properties, so that candy and other foods remain intact after being torn open.
[0038] According to a second aspect of the present invention, there is provided a method for preparing the above-mentioned composite film, comprising the following steps: S1. preparing a first masterbatch, a second masterbatch and a third masterbatch for preparing a bonding layer, an intermediate barrier layer and a heat-sealing anti-sticking layer respectively, and making the first masterbatch, the second masterbatch and the third masterbatch into a first masterbatch, a second masterbatch and a third masterbatch respectively; S2. simultaneously melt-extrude the first masterbatch, the second masterbatch and the third masterbatch and blow-form them, and cool them to obtain a composite film; the first masterbatch forms a bonding layer, the second masterbatch forms an intermediate barrier layer, and the third masterbatch forms a heat-sealing anti-sticking layer.
[0039] Preferably, in S2, during the melt extrusion molding of the first masterbatch, the processing temperature of the first extruder is 40~200℃; during the melt extrusion molding of the second masterbatch, the processing temperature of the second extruder is 40~200℃; during the melt extrusion molding of the third masterbatch, the processing temperature of the third extruder is 40~200℃; the die head temperature of the co-extrusion is 180~220℃.
[0040] The melt extrusion temperature of polymer film has a significant impact on the expansion effect of the extrudate, material properties and product quality. First, at low shear rates, the expansion ratio of the extrudate is related to the temperature of the melt. The higher the temperature, the faster the relaxation of the oriented molecules, resulting in a decrease in the expansion ratio with increasing temperature. Excessive expansion effect of the extrudate may lead to inaccurate product dimensions and affect the final performance of the product. On the contrary, if the expansion effect is too small, it may mean that the flow and orientation of the polymer melt in the mold are insufficient, which will also affect the quality and performance of the product. Secondly, too high a temperature may cause the resin to decompose and the film to become brittle, while too low a temperature may cause poor plasticization of the resin, affecting the tensile strength and surface gloss of the film. In addition, increasing the mold temperature can improve the fluidity of the material, reduce the formation of defects such as bubbles and shrinkage cavities, and improve the surface finish and dimensional accuracy of the product. At the same time, appropriate mold temperature can also promote crystallization and improve the crystallinity and heat resistance of the product. However, too high a temperature may lead to excessive crystallization and make the product brittle. Therefore, in the production process, controlling each melt extrusion temperature within the above range can ensure that the quality and performance of the product meet the expected standards.
[0041] Regarding the composite film provided by the present invention, the function of the bonding layer is to enable the film to be bonded to the aluminum foil through the adhesive; the intermediate barrier layer is to prevent the adhesive from migrating to the food contact layer and the food from migrating to the composite layer; the heat-sealing anti-sticking layer is to achieve the heat-sealing property of the material and the anti-sticking property mentioned in this patent.
[0042] According to a third aspect of the present invention, there is provided a packaging material, comprising the above-mentioned composite film and aluminum foil, wherein the composite film and the aluminum foil are bonded by an adhesive.
[0043] According to a fourth aspect of the present invention, a method for packaging jelly candies is provided, wherein the jelly candies are packaged in blisters sealed by the above-mentioned packaging material.
[0044] According to a fifth aspect of the present invention, there is provided a use of the above composite film in packaging.
[0045] According to the sixth aspect of the present invention, there is provided an application of the above-mentioned composite film in the packaging of gel candy. The composite film provided by the present invention is used to package gel candy, which can improve the anti-sticking effect of the inner layer of the composite on the gel candy, effectively maintain the integrity of the gel candy, and improve the preservation effect. In particular, since the oil-in-water candy is more viscous due to the separation of oil from the water, the composite film provided by the present invention has a more obvious anti-sticking effect when applied to the oil-in-water gel candy.
[0046] Preferably, the application of the above-mentioned composite film in the packaging of gel candy includes the following steps: step one, preparing a preformed blister of aluminum-containing composite hard sheet material by cold forming process; step two, pouring the gel candy raw material into the preformed blister of aluminum-containing composite hard sheet material, and then heat-sealing the composite film on the preformed blister of aluminum-containing composite hard sheet material; wherein, the heat-sealing anti-sticking layer of the composite film is used to perform heat sealing with the preformed blister of aluminum-containing composite hard sheet material.
[0047] Preferably, the surface of the bonding layer in the composite film is also subjected to corona treatment; and an aluminum foil is arranged on the bonding layer after the corona treatment, and the bonding layer and the aluminum foil are bonded by an adhesive; and the adhesive layer includes polyurethane.
[0048] In summary, in the composite film provided by the present invention, its heat-seal anti-sticking layer or heat-seal anti-sticking layer and the intermediate barrier layer are added with inorganic and organic micron particles, and siloxane compounds are introduced into the heat-seal anti-sticking layer at the same time. Through multiple interactions, the surface tension of the inner layer of the composite layer (heat-seal anti-sticking layer) is effectively reduced, thereby effectively reducing the contact angle between the candy or other food and the inner layer of the composite film, so that the inner layer of the composite film has good anti-sticking properties for candy, especially water-in-oil gel candy, and can effectively maintain the integrity of candy or other food after opening the package. At the same time, it can also make the packaging prepared by the subsequent composite film have better tearing performance, and after replacing the traditional heat-seal glue (heat-seal glue is not suitable for this type of packaging, and the heat-seal glue components are easy to migrate into the contents, thereby causing food safety problems), there is still good opening performance, the opening performance is significantly improved, and the candy is intact after opening without obvious damage. That is, the composite film provided by the present invention can simultaneously achieve the three effects of easy opening (easy to tear), anti-sticking, and no glue migration. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 FIG. 1 is a schematic diagram of the structure of a composite membrane in one embodiment of the present invention.
[0050] Figure 2 This is a schematic diagram of the adhesion between the candy and the inner layer of the blister in Comparative Example 4 of the present invention.
[0051] Figure 3 Schematic diagram of the adhesion between the candy and the inner layer of the blister in Example 1 of the present invention.
[0052] Figure 4 Schematic diagram of the adhesion between the candy and the inner layer of the blister in Example 2 of the present invention.
[0053] Figure 5 The following is a diagram showing the method of judging the different adhesion levels of candies in the present invention. DETAILED DESCRIPTION
[0054] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments.
[0055] Example 1 The composite membrane structure of this embodiment is as follows Figure 1 As shown, 1. The raw materials of the bonding layer, the intermediate barrier layer and the heat-sealing anti-sticking layer are as follows: Raw materials for the bonding layer: 60 kg of low-density polyethylene resin (2426H, produced by Sinopec, melting point 110°C, melt index 1.9, density 0.924 g / cm³), 10 kg of adhesive polyolefin resin (ADMER NF108, produced by Mitsui, Japan, melting point 120°C, melt index 1.6, density 0.92 g / cm³), 30 kg of linear low-density polyethylene resin (1002AY, produced by ExxonMobil, USA, melting point 121°C, melt index 2, density 0.918 g / cm³); the above raw materials are granulated by water-stranded strips using relevant equipment and then dried, with the output controlled at 200 kg / hour to obtain the first masterbatch.
[0056] Raw materials for the intermediate barrier layer: 40 kg of low-density polyethylene resin (2426H, produced by Sinopec, melting point 110°C, melt index 1.9, density 0.924 g / cm³), 10 kg of adhesive polyolefin resin (Admer NF528A, produced by Mitsui, Japan, melting point 100°C, melt index 4.0, density 0.91 g / cm³), 30 kg of metallocene polyethylene resin (2045.11G, produced by Dow, USA, melting point 122°C, melt index 1.0, density 0.922 g / cm³), 10 kg of food-grade calcium carbonate (produced by Jiangxi Chuangxian Fine Calcium Industry, 8000 mesh), 10 kg of talcum powder (produced by Liaoning Xinda, model SDC-9272, 2000 mesh); 2426H, Admer NF528 and 2045.11G were first ground into fine powders under liquid nitrogen, with a powder particle size of 300 mesh, and then the moisture was dried in an oven to less than 0.5%; then the ground and dried 2426H, Admer NF528, 2045.11G were put into a high-speed stirrer together with food-grade calcium carbonate and talcum powder for stirring at a speed of 2000 rpm and a temperature of 60°C. After high-speed stirring for 40 minutes, all the materials were sucked into the hopper of the twin-screw extruder through a pipeline. The plastic strips coming out of the twin screw were water-cooled (temperature at 20°C), sheared, dried and granulated at a drying temperature of 80°C to obtain the second masterbatch.
[0057] Among them, in the preparation process of the above-mentioned second masterbatch, the twin-screw extruder model is: Nanjing Kailida Machinery Equipment Co., Ltd. TSE-52B co-rotating parallel twin-screw blending extruder granulator, and the specific parameters are shown in Table 1: Table 1 Specific extrusion parameters of twin-screw extruder
[0058] Raw materials for heat-seal anti-sticking layer: 30 kg of low-density polyethylene resin (2426H, produced by Sinopec, melting point 110°C, melt index 1.9, density 0.924 g / cm³), 45 kg of metallocene polyethylene resin (2045.11G, produced by Dow Chemical, USA, melting point 122°C, melt index 1.0, density 0.922 g / cm³), 20 kg of siloxane polymer (produced by Zhejiang Jiahua Fine Chemical Co., Ltd., model Javachem PSA-300, melting point 105°C, melt index 300, density 0.96 g / cm³), 3 kg of silicon dioxide (produced by PQCORPORATION, model HP 230, D50 is 3.6μm, oil absorption is 250g / 100g), and 3 kg of ultra-high molecular weight polyethylene (MIPELON PM200, produced by Mitsui, Japan, D50 is 10μm, melting point 121℃, molecular weight 2 million, density 0.94g / cm³) 2 kg; 2426H, 2045.11G, and Javachem PSA-300 (siloxane polymer) were ground into fine powders under liquid nitrogen, with a powder particle size of 300 mesh, and then dried in an oven to a moisture content of less than 0.5%. -300 (siloxane polymer) powder and silicon dioxide are stirred at high speed (so that the surface hydroxyl groups of siloxane and silicon dioxide complete partial polycondensation reaction first, and part of the silane polymer itself is reactive hydroxymethyl, which can undergo polycondensation reaction with the surface hydroxyl groups of silicon dioxide to remove methanol and increase the binding force of the two substances). The high-speed stirring equipment controls the temperature at 80°C and the stirring time is 15 minutes. Then add the above-ground 2426H, metallocene 2045.11G, and MIPELONPM200 (ultra-high molecular weight polyethylene) and continue to stir and mix at high speed for 30 minutes. The speed is 1200 rpm and the temperature is controlled at 60°C. Then, it is sucked into the twin-screw hopper through the pipeline. After the plastic strips coming out of the twin screw are cooled by water (temperature at 20°C), they are sheared, dried and granulated at a drying temperature of 80°C to obtain the third masterbatch.
[0059] Among them, in the preparation process of the third masterbatch, the twin-screw extruder model is: Nanjing Kailida Machinery Equipment Co., Ltd. TSE-52B co-rotating parallel twin-screw blending extruder granulator, and the specific parameters are shown in Table 2: Table 2 Specific extrusion parameters of twin-screw extruder
[0060] 2. Film blowing (preparation of composite films) The first masterbatch, the second masterbatch and the third masterbatch prepared above were added into the three hopper extruders A, B and C of the film blowing compound machine, respectively. The equipment is Wuhan Xinzhongde SXGM-3*1600. The formula is shown in Table 3: Table 3 Relevant formula and thickness parameters for preparing composite films
[0061] The raw materials in Table 3 are heated to a molten state, and the die head is pushed by a screw to form a film tube blank, and air is injected into the tube through a blowing ring. The inflated film is quickly cooled by a cooling ring to fix its size and shape; the cooled film passes through a traction roller and a winder and is rolled into a roll for subsequent processing.
[0062] The specific processing temperature is shown in Table 4: Table 4 Processing temperature for preparing composite films
[0063] At the same time, the surface of the composite membrane bonding layer is treated with corona treatment, the corona adopts 4KW, and the corona machine is more than 42 dynes.
[0064] 3. Aluminum foil composite On the BOBST DA800 laminating machine, a 16-micron thick aluminum foil (supplier: Henan Mingtai, hardness: H18, alloy grade: 8011) was used, and polyurethane glue was applied on its surface. The glue was Henkel 2788, the solid content was 40%, the glue amount was 4.0-4.5gsm, and the oven temperature was 90, 90, and 100°C (three-stage oven temperature). The glue and the corona surface of the composite film prepared above were composited at a composite temperature of 50°C and a speed of 300m / min. After being cured at room temperature for 12 hours after being removed from the machine, it was matured at 40°C for 3 days to obtain an aluminum foil composite film, which was then cut into 250mm widths.
[0065] 4. Candy packaging During packaging, cold-formed aluminum materials are preformed into blisters, and the premixed candies are poured into the cold-formed aluminum blisters at high temperature, and the aluminum foil composite film product prepared in this embodiment is heat-sealed on the blisters at 180-190° C. to complete the packaging process. The packaging equipment is a Shanghai Jiangnan DPP260 blister packaging machine.
[0066] Example 2 The composite membrane structure of this embodiment is as follows Figure 1 As shown, 1. The raw materials of the bonding layer, the intermediate barrier layer and the heat-sealing anti-sticking layer are as follows: Raw materials for the bonding layer: 50 kg of low-density polyethylene resin (FD0474, produced by Kadar Lotrene, melting point 108°C, melt index 4, density 0.923 g / cm³), 5 kg of adhesive polyethylene resin (SF304, produced by Guangzhou Lushan, melting point 112°C, melt index 1.6, density 0.948 g / cm³), 45 kg of low-density linear polyethylene resin (2036G, produced by Dow Chemical, USA, melting point 125°C, melt index 2.5, density 0.935 g / cm³); the above raw materials are granulated by water-stranded strips using relevant equipment and then dried, with the output controlled at 250 kg / hour to obtain the first masterbatch.
[0067] Raw materials for the intermediate barrier layer: 35 kg of low-density polyethylene resin (FD0474 produced by Kadar Lotrene, melting point 108°C, melt index 4, density 0.923 g / cm³), 15 kg of adhesive polyolefin resin (ADMER NF468E, produced by Mitsui, Japan, melting point 120°C, melt index 4, density 0.92 g / cm³), 35 kg of low-density linear polyethylene resin (2036G, produced by Dow Chemical, USA, melting point 125°C, melt index 2.5, density 0.935 g / cm³), 8 kg of food-grade calcium carbonate (produced by Jiangxi Chuangxian Fine Calcium Industry, 10000 mesh), 12 kg of talc (produced by IMIFABI, model HTPultra5, 4000 mesh); FD0474, ADMER NF468E and 2036G were first ground into fine powders under liquid nitrogen with a powder particle size of 300 mesh, and then the moisture was dried in an oven to less than 0.5%; then the ground and dried FD0474, ADMER NF468E, 2036G were put into a high-speed stirrer together with food-grade calcium carbonate and talcum powder for stirring at a speed of 1500 rpm and a temperature of 60°C. After high-speed stirring for 40 minutes, all the materials were sucked into the hopper of the twin-screw extruder through a pipeline. The plastic strips coming out of the twin screw were cooled by water (temperature at 20°C), sheared, dried and granulated at a drying temperature of 80°C to obtain the second masterbatch.
[0068] Among them, in the preparation process of the above-mentioned second masterbatch, the twin-screw extruder model is: Nanjing Kailida Machinery Equipment Co., Ltd. TSE-52B co-rotating parallel twin-screw blending extruder granulator, and the specific parameters are shown in Table 5: Table 5 Specific extrusion parameters of twin-screw extruder
[0069] Raw materials for heat-seal anti-sticking layer: 35 kg of low-density polyethylene resin (FD0474, produced by Kadar Lotrene, melting point 108°C, melt index 4, density 0.923 g / cm³), 45 kg of metallocene polyethylene (8784, produced by ExxonMobil, melting point 121°C, melt index 0.8, density 0.914 g / cm³), 20 kg of siloxane polymer (vinyl trimethoxysilane oligomer, model HP-171, produced by Jiangxi Hongbai New Materials Co., Ltd.), 2 kg of silicon dioxide (produced by Grace, model SYLOBLOC® K 200, D50 is 2.4 μm, oil absorption is 250 g / 100 g), 2 kg of MIPELON XM221U (ultra-high molecular weight polyethylene, produced by Mitsui, Japan, D50 is 25 μm, melting point 136°C, molecular weight 2 million, density 0.94 g / cm³); FD0474, 8784, and siloxane polymer (vinyl trimethoxysilane oligomer) were first ground into fine powders under liquid nitrogen, with a powder particle size of 300 mesh, and then dried in an oven to a moisture content of less than 0.5%; the ground siloxane polymer and silicon dioxide were then stirred at high speed (so that the surface hydroxyl groups of siloxane and silicon dioxide first completed partial polycondensation reaction, and the silane polymer itself also had some reactive hydroxymethyl groups, which could undergo polycondensation reaction with the surface hydroxyl groups of silicon dioxide to remove methanol and increase the binding force of the two substances), the high-speed stirring equipment controlled the temperature at 80°C, and the stirring time was 15 minutes; then the ground FD0474, 8784, and MIPELON XM221U (ultra-high molecular weight polyethylene) continues to be stirred at high speed for 30 minutes, the speed is 1200 rpm, the temperature is controlled at 60°C, and then it is sucked into the twin-screw hopper through the pipeline. The plastic strips coming out of the twin screw are cooled by water (temperature at 20°C), sheared, dried and granulated at a drying temperature of 80°C to obtain the third masterbatch.
[0070] Among them, in the preparation process of the third masterbatch, the twin-screw extruder model is: Nanjing Kailida Machinery Equipment Co., Ltd. TSE-52B co-rotating parallel twin-screw blending extruder granulator, and the specific parameters are shown in Table 6: Table 6 Specific extrusion parameters of twin-screw extruder
[0071] 2. Film blowing (preparation of composite films) The first masterbatch, the second masterbatch and the third masterbatch prepared above were added into the three hopper extruders A, B and C of the film blowing compound machine, respectively. The equipment is Wuhan Xinzhongde SXGM-3*1600. The formula is shown in Table 7: Table 7 Relevant formula and thickness parameters for preparing composite films
[0072] The raw materials in Table 7 are heated to a molten state, and the die head is pushed by a screw to form a film tube blank, and air is injected into the tube through a blowing ring. The inflated film is quickly cooled by a cooling ring to fix its size and shape; the cooled film passes through a traction roller and a winder and is rolled into a reel for subsequent processing.
[0073] The specific processing temperature is shown in Table 8: Table 8 Processing temperature for preparing composite films
[0074] At the same time, the surface of the composite membrane bonding layer is treated with corona treatment, the corona adopts 4KW, and the corona machine is more than 42 dynes.
[0075] 3. Aluminum foil composite On the BOBST DA800 laminating machine, a 20-micron thick aluminum foil (supplier: Henan Wanji, hardness: H18) was used, and polyurethane glue was applied on its surface. The glue was Gaomeng 3166, the solid content was 40%, the glue amount was 3.0-3.5gsm, and the oven temperature was 90, 90, and 100°C (three-stage oven temperature). The glue and the corona surface of the composite film prepared above were composited. The composite temperature was 50°C and the speed was 300m / min. After being cured at room temperature for 12 hours after being removed from the machine, it was matured at 40°C for 3 days to obtain an aluminum foil composite film, which was then cut into 250mm widths.
[0076] 4. Candy packaging During packaging, cold-formed aluminum material is preformed into blisters, and the premixed candies are poured into the cold-formed aluminum blisters at high temperature, and the aluminum foil composite film product prepared in this embodiment is heat-sealed on the blisters at 180-190° C. to complete the packaging process. The packaging equipment is a Shanghai Jiangnan DPP260 blister packaging machine.
[0077] Example 3 The difference between this embodiment and embodiment 1 is that the raw material of the heat-sealing anti-sticking layer uses the same amount of silica microspheres with a D50 of 15 μm produced by Fucai Mineral Products Co., Ltd.; the rest is the same as embodiment 1.
[0078] Example 4 The difference between this embodiment and embodiment 1 is that the raw materials of the intermediate barrier layer use the same proportions of calcium carbonate with a particle size of 800 mesh (produced by Jiangxi Hengshengtai Co., Ltd.) and talc powder with a particle size of 1000 mesh (produced by Shandong Kaiwell); the rest is the same as embodiment 1.
[0079] Example 5 The difference between this embodiment and the first embodiment is that the inorganic filler B, that is, calcium carbonate and talcum powder are not added to the raw materials of the intermediate barrier layer; the rest is the same as the first embodiment.
[0080] Example 6 The difference between this embodiment and embodiment 1 is that no bonding layer raw material is prepared, that is, the prepared composite film only has an intermediate barrier layer and a heat-sealing anti-layer; the rest is the same as embodiment 1.
[0081] It should be noted here that when there is no bonding layer, during the blown film molding process, during the extrusion process using an extruder, only double-layer extrusion is required, and the thickness ratio of the intermediate barrier layer and the heat-sealing anti-layer is also 4:3, and the total thickness of the composite film is also 30μm, and the rest remains unchanged.
[0082] Example 7 The difference between this embodiment and embodiment 1 is that no intermediate barrier layer material is prepared, that is, the prepared composite film only has a bonding layer and a heat-sealing anti-layer. The rest is the same as embodiment 1.
[0083] It should be noted here that when there is no intermediate barrier layer, during the blown film molding process, during the extrusion process using an extruder, only double-layer extrusion is required, and the thickness ratio of the bonding layer and the heat-sealing anti-layer is also 1:1, and the total thickness of the composite film is also 30μm, and the rest remains unchanged.
[0084] Comparative Example 1 The difference between this comparative example and Example 1 is that no anti-sticking material, that is, no silicone polymer, is added to the raw materials of the heat-sealing anti-sticking layer; the rest is the same as Example 1.
[0085] Comparative Example 2 The difference between this comparative example and Example 1 is that the raw materials of the heat-sealing anti-sticking layer do not contain anti-sticking material and inorganic filler A, that is, do not contain siloxane polymer and silicon dioxide; the rest is the same as Example 1.
[0086] Comparative Example 3 The difference between this comparative example and Example 1 is that no ultra-high molecular weight polyethylene, that is, no MIPELON PM200, is added to the raw materials of the heat-sealing anti-sticking layer; the rest is the same as Example 1.
[0087] Comparative Example 4 The blister packaging used in this comparative example is a standard structure of OP / AL20 / HSL4GSM.
[0088] The specific preparation process of the standard structure is as follows: select aluminum foil (Henan Mingtai Aluminum, H18 series, alloy grade 8011, thickness 20um) to unwind, apply heat sealing glue (Shanghai Weike VC1100A), the wet glue coating amount is 20 grams, cool after passing through an oven, and then apply OP protective varnish (Shanghai Weike OP1302D) with a wet glue coating amount of 3 grams to obtain a standard PTP cover film with the following structure.
[0089] Comparative Example 5 This comparative example uses a common composite PE film, and the formula is shown in Table 9: Table 9 Common composite PE film formula
[0090] Other processing conditions were the same as those in Example 1, including film blowing, aluminum foil lamination, and candy packaging.
[0091] It should be noted here that 2420H and 2426H are low-density polyethylene resins produced by Sinopec; 1002KW is a linear low-density polyethylene resin produced by ExxonMobil.
[0092] Test Case 1. Experimental Construction Method The aluminum foil composite films containing aluminum foil structures prepared in all the above embodiments and comparative examples were tested for burst resistance, contact angle, and anti-sticking performance. The specific testing methods are as follows: (1) Burst resistance test method: Refer to GB / T 454-2020 "Determination of burst resistance of paper", cut the film into samples of size 100×100mm, and the sample should not have folds, wrinkles, visible cracks or other obvious damage. Place the sample on the test instrument, and the machine gradually applies pressure until the sample breaks. Record the maximum force value when the sample breaks. The test result is the average of 10 valid results, which is the film burst resistance. Blister packaging is usually used from the inside out, and the burst resistance is judged by the force value in this direction.
[0093] (2) Contact angle test method: refer to GB / T 32652-2016 "Contact angle measurement method for films and film materials", heat the water-in-oil gel candy to 70℃ to melt it into liquid, quantitatively drip 10 μl of the liquid on the surface of the composite film (heat-sealing anti-sticking layer), use a contact angle meter to capture the side image of the droplet on the film surface, and analyze the contact angle of the droplet at the point where it contacts the film surface; each test object is tested three times and the average value is taken.
[0094] (3) Anti-sticking performance test method: pour the oil-in-water gel candy (liquid) into a cold-formed aluminum blister and use the prepared aluminum-plastic composite film to heat-seal (to prevent the candy from losing moisture), so that the candy is in full contact with the composite film (heat-seal anti-sticking layer); place the candy at 40°C for 240 hours, and then completely cool it to room temperature (25°C, cooling for more than 4 hours), open the composite film material, and check the degree of adhesion between the composite film material and the candy (measured in the number of adhered particles), and refer to Figure 5 , to judge different degrees of adhesion.
[0095] 2. Experimental results The test results of the bursting resistance, contact angle and anti-sticking performance of the composite films prepared in all the above embodiments and comparative examples are shown in Table 10.
[0096] Table 10 Test data of burst resistance, contact angle and anti-sticking property of aluminum-plastic composite film in the examples and comparative examples
[0097] It can be seen from Table 10 that the contact angle between the aluminum foil pre-coated with glue (Comparative Example 4) and the water-in-oil gel candy (liquid) is 65~75°, the contact angle between the ordinary composite film (Comparative Example 5) and the candy (liquid) is 70~80°, and the contact angle between the composite film of the present patent (Examples 1~7) and the candy (liquid) is improved to 80~95°.
[0098] After packaging candies with aluminum foil pre-coated with glue, ordinary composite film, and the composite film of the present invention, they were treated at a constant temperature of 40°C for 240 hours (10 days), cooled back to room temperature, and opened. The candies with the composite film of the present invention had no obvious adhesion, and the adhesion ratio was low. The adhesion ratios of aluminum foil pre-coated with glue and ordinary composite film were 100% (Comparative Examples 4 and 5). And it can be seen from Figure 2 It can be seen that the adhesion between the candy and the inner layer of the blister in Comparative Example 4 is more serious, while Figure 3 and Figure 4 It can be seen that there is basically no adhesion between the candy and the inner layer of the blister in Examples 1 and 2. In addition, the bursting strength of the composite film of the present invention is relatively moderate, so that the composite film is easy to puncture or tear, and can also avoid rupture during the packaging process or other transportation processes, which is not conducive to processing and is not conducive to the protection and preservation of the candy.
[0099] In addition, the raw materials of the heat-seal anti-sticking layer of the composite film in Comparative Example 1 do not contain anti-sticking materials (siloxane polymers), the heat-seal anti-sticking layer in Comparative Example 2 does not contain anti-sticking materials (siloxane polymers) and inorganic fillers (silicon dioxide), and the heat-seal anti-sticking layer in Comparative Example 3 does not contain ultra-high molecular weight polyethylene, which all cause the anti-sticking properties of the composite films to decrease after packaging candies (the contact angles are significantly reduced), which shows that these materials have an important influence on the anti-sticking properties of the composite films, especially on the formation of micro-nano surface concave-convex points, thereby affecting the anti-sticking properties of the composite films.
[0100] Furthermore, comparing Example 1 with Example 3, the particle size of the inorganic filler A in the heat-sealing barrier layer of Example 3 is too large, and the specific surface area is too large, which may cause the candy to adhere to the inorganic filler, thereby causing the anti-sticking performance of the aluminum foil composite film to decrease.
[0101] Comparing Example 1 with Example 4, the mesh size of the inorganic filler B in the middle barrier layer of Example 4 is relatively small and the particle size is relatively large, which will cause the bursting resistance of the aluminum foil composite film to decrease, and will also affect the raised surface of the heat sealing layer, thereby worsening the adhesion and reducing the contact angle, resulting in a decrease in the anti-sticking performance of the aluminum foil composite film.
[0102] Comparing Example 1 and Example 5, the intermediate barrier layer in Example 5 does not contain the inorganic filler B, which will greatly increase the burst resistance. At the same time, PE is adhered, and customers cannot open the aluminum foil composite film well.
[0103] Comparing Example 1 and Example 6, the composite film of Example 6 does not have a bonding layer. Although it also has good anti-sticking properties, in actual application, the composite film without a bonding layer has a poor composite effect with the aluminum foil and is prone to stratification, which causes the aluminum foil composite film to break more easily, which will have a certain adverse effect on actual packaging.
[0104] Comparing Example 1 with Example 7, the composite film of Example 7 does not have an intermediate barrier layer. Due to the absence of this barrier layer, firstly, it will affect the burst resistance and the opening effect, and at the same time, it cannot affect the surface micro-nano structure of the heat-sealing layer, thereby greatly reducing the anti-sticking effect.
[0105] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.
Claims
1. A composite film, characterized in that: It includes a heat-sealing anti-sticking layer; the heat-sealing anti-sticking layer includes an anti-sticking material, an inorganic filler A, a polyolefin A, and an ultra-high molecular weight polyethylene; the anti-sticking material includes an organic silicon compound; The D50 of the inorganic filler A is 1-10 μm; and the inorganic filler A includes silicon dioxide.
2. The composite film according to claim 1, characterized in that: The mass ratio of the anti-sticking material, the inorganic filler A, the polyolefin A, and the ultra-high molecular weight polyethylene is 2-30:1-10:50-80:1-10.
3. The composite membrane according to claim 1, characterized in that: The organosilicon compound includes a siloxane polymer.
4. The composite film according to claim 1, characterized in that: In the heat-sealing anti-sticking layer, the particle size of the ultra-high molecular weight polyethylene is 1-40 μm.
5. The composite film according to claim 1, characterized in that: In the heat-seal anti-sticking layer, the polyolefin A independently includes at least one of polyethylene and polypropylene.
6. The composite membrane according to claim 5, characterized in that: In the heat-sealing anti-sticking layer, When the polyolefin A includes the polyethylene, the polyethylene includes low-density polyethylene and metallocene polyethylene, and the mass ratio of the low-density polyethylene to the metallocene polyethylene is 20-60:20-60; or, the polyethylene includes the low-density polyethylene and linear low-density polyethylene A, and the mass ratio of the low-density polyethylene to the linear low-density polyethylene A is 20-60:20-60; When the polyolefin A includes the polypropylene, the polypropylene includes homopolymer polypropylene, binary material, and ternary material, and the mass ratio of the homopolymer polypropylene, the binary material, and the ternary material is 10-30:20-30:40-60; The binary material includes a polyolefin material formed by copolymerization of two monomers; the ternary material includes a polyolefin material formed by copolymerization of three monomers.
7. The composite film according to any one of claims 1 to 6, characterized in that: It also includes an intermediate barrier layer; the intermediate barrier layer includes an inorganic filler B and a polyolefin B, and the mass ratio of the inorganic filler B to the polyolefin B is 10-80:20-90.
8. The composite membrane according to claim 7, characterized in that: In the intermediate barrier layer, the inorganic filler B includes at least one of calcium carbonate, talc, mica, and silicon dioxide; the particle size of the inorganic filler B is not less than 1250 mesh; The polyolefin B independently includes at least one of polyethylene and polypropylene.
9. The composite membrane according to claim 8, characterized in that: The intermediate barrier layer further includes a first compatibilizer and a lubricant; the mass ratio of the inorganic filler B, the polyolefin B, the first compatibilizer, and the lubricant is 10-80:20-90:1-10:0-5; The first compatibilizer includes at least one of maleic anhydride modified polyolefin and acrylic acid modified polyolefin; The lubricant includes at least one of calcium stearate, magnesium stearate and polyethylene wax.
10. The composite membrane according to claim 7, characterized in that: It also includes a bonding layer, which includes polyolefin C and a second compatibilizer, and the mass ratio of the polyolefin C to the second compatibilizer is 10~90:10~90.
11. A packaging material, characterized in that: It comprises the composite film and aluminum foil as described in any one of claims 1 to 10, wherein the composite film and the aluminum foil are bonded to each other by an adhesive.
12. A method for packaging gel candy, characterized in that: The jelly candy is packaged in blisters sealed by the packaging material as claimed in claim 11.
13. Use of the composite film according to any one of claims 1 to 10 in packaging.
14. Use of the composite film according to any one of claims 1 to 10 in packaging of gel candies.
15. The use of the composite film as claimed in claim 14 in the packaging of gel candy, characterized in that: The steps include: Step 1, preparing a preformed blister of aluminum-containing composite hard sheet material by cold forming process; Step 2: pouring the gel candy raw material into the preformed blister of the aluminum-containing composite hard sheet material, and then heat-sealing the composite film on the preformed blister of the aluminum-containing composite hard sheet material; wherein, the heat-sealing anti-sticking layer of the composite film is used to heat-seal the preformed blister of the aluminum-containing composite hard sheet material.
Citation Information
Patent Citations
Aluminum foil sealing cover and manufacturing method thereof
CN118076330A
BOPP (Biaxially-oriented Polypropylene) heat-sealing film and preparation method thereof
CN118952803A
Lid material
JP2017171338A
Sealant film having adhesion prevention property of ingredient
JP2019010803A
Seal layer, laminate, laminate for package, and packaging bag
JP2020172294A